2007
DOI: 10.4049/jimmunol.179.7.4775
|View full text |Cite
|
Sign up to set email alerts
|

IFN Regulatory Factor 8 Mediates Apoptosis in Nonhemopoietic Tumor Cells via Regulation of Fas Expression

Abstract: IRF8 is a transcription factor that was originally identified in myeloid cells. Mice with a null mutation of IRF8 exhibit uncontrolled expansion of myeloid cells that progress into a phenotype resembling human chronic myelogenous leukemia (CML). In human patients with CML, IRF8 transcript levels are frequently diminished. Here, we report that disruption of IRF8 function diminished Fas‐mediated apoptosis in solid tumor cells. Furthermore, it was found that constitutively expressed IRF8 is associated with the Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 56 publications
1
51
0
Order By: Relevance
“…A previous study has shown that Bcl-xL expression is regulated by IRF8 in myeloid leukemia cell lines (43), and our previous study has shown that Bax and Fas are transcriptionally regulated by IRF8 in myeloid cells and in nonhematopoietic cells (40,44). We, therefore, reasoned that altered expression of Fas, Bax, and Bcl-xL might be due to altered IRF8 expression in MDSCs.…”
Section: Irf8 Is Down-regulated In Tumor-induced Mdscs In Vivo-mentioning
confidence: 88%
“…A previous study has shown that Bcl-xL expression is regulated by IRF8 in myeloid leukemia cell lines (43), and our previous study has shown that Bax and Fas are transcriptionally regulated by IRF8 in myeloid cells and in nonhematopoietic cells (40,44). We, therefore, reasoned that altered expression of Fas, Bax, and Bcl-xL might be due to altered IRF8 expression in MDSCs.…”
Section: Irf8 Is Down-regulated In Tumor-induced Mdscs In Vivo-mentioning
confidence: 88%
“…For examples, IRF8 forms a complex with PU.1 to activate the transcription of p15 INK4B /CDKN2B, a bona fide TSG, in murine myeloid cells in response to IFNaˆtreatment (Schmidt et al, 2004). IRF8 also induces the expression of multiple TSGs such as NF1 (Zhu et al, 2004;Tamura et al, 2005) and apoptotic genes such as FAS (Yang et al, 2007a, b), and represses the expression of the oncogenic BCR/ABL and antiapoptotic BCL2 (Tamura et al, 2003;Burchert et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…12 To substantiate these findings, we investigated a cohort of 100 patients with myeloid malignancies that had been characterized cytogenetically (Supplementary Table S3 lead to a loss of wild-type function in in vitro and in vivo models. 5,6,16 We analysed these exons by direct sequencing in 68 patients from whom material was available (Supplementary Materials and Methods). We found unaltered sequences in almost all analysed patients.…”
Section: Conflict Of Interestmentioning
confidence: 99%